ANALISIS KECENDERUNGAN PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR - Harjito, Yunus (Jurnal Akuntansi, 2015)
This study aims to predict the effect of audit quality, financial condition, the growth of the company, the previous year's audit opinion, firm size, and a debt-to-equity ratio of the tendency of going-concern audit opinion. In this study, the type of data used is quantitative data with a population of 145 companies listed in the Indonesia Stock Exchange in 2008-2012. The analytical method used is logistic regression analysis with a sample totalling 20 companies were selected based on the purposive sampling method for 5 periods. Based on the analysis it can be concluded that the quality of the audit significant negative effect on the going-concern audit opinion, the financial condition of the company has no significant effect on the going-concern audit opinion, the growth of the company has no significant effect on the going-concern audit opinion, the previous year's audit opinion has no effect significantly to the going-concern audit opinion, the size of the company does not have a significant effect on the going-concern audit opinion, and the debt-to-equity ratio does not significantly influence the going-concern audit opinion.